Fear of Missing Out dan Subjective Well-Being pada Karyawan Muda Pengguna Media Sosial di Kabupaten Semarang - Fenisia Dwi Pangesti; Sutarto Wijono (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Fear of Missing Out (FOMO) has become increasingly relevant in the workplace because digital connectivity exposes employees to continuous streams of social and occupational information. Although prior studies generally report that FOMO is associated with lower subjective well-being, evidence in employee populations remains limited, particularly in local industrial contexts. This study aimed to examine the relationship between FOMO and subjective well-being among employees in Semarang Regency. A quantitative correlational design was applied. The participants were 373 employees aged 19-30 years who used social media for at least two hours per day, selected using purposive sampling supported by snowball sampling. FOMO was measured using the Indonesian adaptation of the FOMO scale developed from Mazlum and Atalay's framework, while subjective well-being was measured through the Satisfaction with Life Scale and Positive Affect and Negative Affect Schedule. Data were analyzed using descriptive statistics, validity and reliability tests, normality and linearity tests, and Spearman's rho correlation because the data were not normally distributed. The results showed that most participants had moderate FOMO and high subjective well-being. The correlation test indicated a positive and significant relationship between FOMO and subjective well-being (r = 0.105; p = 0.042), although the effect size was very weak and contrary to the initial hypothesis. These findings suggest that FOMO does not necessarily reduce employees' well-being; in certain contexts, it may function as a mild social awareness signal that encourages connection, information seeking, and adaptive engagement. The study contributes to the literature by highlighting a context-specific and non-linear interpretation of FOMO in working adults. Practical implications include the need for workplace well-being programs, digital self-regulation training, and organizational support to prevent FOMO from developing into maladaptive anxiety.